Bahasa sebagai Alat Integrasi dan Disintegrasi Sosial: Studi Multikultural - Siti Fatma Rahmawati; Andi Ahmad Fauzan; Dewi Sita Lestari (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2026)
Language plays a dual role in multicultural societies, functioning both as a mechanism of social integration and as a potential source of social disintegration. This study aims to analyze the role of language in shaping social cohesion, identity construction, and intercultural relations in diverse sociocultural contexts. The research employs a qualitative literature review approach by synthesizing findings from international journals, book chapters, dissertations, and repositories indexed by DOI sources. Data were analyzed using thematic content analysis focusing on language, identity, integration, and social fragmentation. The findings reveal that language promotes inclusion through multilingual education, intercultural communication, and identity affirmation (Arifi, 2024; Mouboua et al., 2024; Oksaar, 1992), while simultaneously creating social boundaries when linguistic hierarchies and exclusionary policies occur (Dooly & Unamuno, 2009; Calinon, 2013). Furthermore, language shifts in migrant communities demonstrate both adaptive integration and cultural erosion (Akintayo et al., 2024; Mocanu & Bibiri, 2023). The study concludes that inclusive multilingual policies and intercultural competence are essential to maximizing language as a tool for integration while minimizing its disintegrative effects.